The Effect of Loss Aversion Bias and Regret Aversion Bias on Financial Decisions with Financial Literacy as an Intervening Variable - Fazlur Rahman Rahawarin (Profesional Muda Cendekia Publishing, 2023)
Decision-making is difficult for everyone, including MSMEs. This study describes the relationship between behavioral bias, namely loss aversion bias and regret aversion bias on decision making. Financial literacy becomes an intervening variable in explaining the relationship between the two. This study took 125 SMEs in Bululawang using a questionnaire. Data analysis was performed using SEM analysis and using the AMOS application. The results show that loss aversion bias and regret aversion bias affect investment decision-making. Likewise, financial literacy can be an intervening variable that can affect the relationship between the two